The first blush of tasting: Porcellio scaber isopod and Enchytraeus albidus enchytraeid prefer the leaf litter of invasive over native plant species - R. Petrikovszki; G. Boros (The European Zoological Journal)
The establishment of invasive plants is a very serious threat from an ecological point of view, through decreasing biodiversity and a changing ecosystem, which affect decomposition processes. We carried out no-choice feeding experiments with Porcellio scaber and Enchytraeus albidus individuals. Three different plant species (Acer platanoides as control, Asclepias syriaca and Solidago gigantea) were offered for both decomposer species. Carbon and nitrogen contents, and the C:N ratio of the plant species, were determined as well. Both leaf loss and weight gain showed that Asclepias was the most suitable food source for isopods. In the case of enchytraeids, the rate of leaf loss was significantly higher for Asclepias, followed by Solidago and Acer. In addition, the highest N content and the lowest C:N ratio were determined for Asclepias leaves. All the above-presented observations show that in vegetation consisting of many plant species, the decomposition of possibly appearing invasive species can occur faster; thus, the inorganic N supply in their immediate environment can also increase as a consequence of the increased amount of excreta of the decomposing organisms. This may allow for more intensive growth and more efficient spread, which gives invasive species another strategic advantage over natives.